RISK FACTORS AND OUTCOME OF OLIGOHYDRAMNIOS: OUR EXPERIENCE AT A TERTIARY CARE HOSPITAL. : JPUMHS;2024:14:04,250 257. http://doi.org/10.46536/jpumhs/2024/14.04.585 - Nafeesa Ghani1, Chandnee Rehman2, Nazia Noushin3, Noreen Afsar4, Samra Bashir5 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Oligohydramnios, the condition of having less than the normal volume of amniotic fluid, is a complication of 1-5% of pregnancies. It is associated with high risks of perinatal morbidity and mortality. It has many causes, often related to maternal factors like hypertension, diabetes, post-term pregnancy, and premature rupture of membranes PROM. Data with regards to the risk factors and neonatal outcomes in our region still seems incomplete despite its significance in clinical practice. OBJECTIVE: To evaluate the risk factors associated with oligohydramnios and analyze its impact on perinatal outcomes at a tertiary care hospital. METHODS: This prospective observational study was carried out at the Department of Obstetrics & Gynecology, Hayatabad Medical Complex Peshawar, from 1st March 2021 to March 2022. Total 152 pregnant women with oligohydramnios AFI ≤5 cm or SDP <2 cm at ≥28 weeks gestation was enrolled. Data on demographics, risk factors, ultrasound findings, delivery mode, and neonatal outcomes were recorded on a predefined proforma. Statistical analysis was performed using SPSS 25.0. RESULTS: The mean maternal age was 27.4 ± 4.8 years; 64.5% of women were aged 20–30 years. Hypertensive disorders 30.3% were the most frequent maternal risk factor, followed by post-term pregnancy 21.1% and PROM 18.4%. Isolated oligohydramnios occurred in 25.7% of cases. Abnormal Doppler flow was found in 29.6%. Cesarean section was the commonest delivery mode 58.6%, often due to fetal distress. Adverse outcomes included low birth weight 40.1%, NICU admission 25.0%, low Apgar scores 14.5%, stillbirth 3.3%, and early neonatal death 2.0%. Hypertensive disorders, PROM, and abnormal Doppler flow were significantly associated with poor perinatal outcomes. CONCLUSION: The presence of oligohydramnios represents a high risk for negative perinatal outcomes, especially when linked with hypertension, premature rupture of the membranes PROM, and abnormal fetal Doppler ultrasound results. Early diagnosis and corrective actions are crucial in decreasing complications and enhancing neonatal results.